Optical and laser properties of Ti-sapphire grown by different methods in reducing medium - Kryvonosov, E.V.; Nizhankovskiy, S.V.; Lytvynov, L.A.; Bui, A.A. (Functional Materials, 2012)
Optical and laser properties of Ti-sapphire grown in reducing gaseous medium are studied. It is shown that HDSM-crystals have satisfactory functional characteristic and can be used for the making of wide-aperture laser elements with wide diameter of 25-50 mm. Minimum distortion of the wave front (0.1λ) and FOM-factor of 200-250 are characteristic of the elements with the ends oriented parallel to the crystallization front of the initial crystal annealed in reductive medium with the reduction potential e ≈ -180...-230 kJ/mol.